ANALISIS BAKTERI Coliform, Esherichia coli, dan Salmonella sp. PADA OLAHAN MAKANAN MANDAI DARI KULIT BUAH CEMPEDAK (Artocarpus integer) DI KOTA SAMARINDA - Dianita, Feby; Akhmad; Sari, Eadvin Rosrinda Awang (Universitas Muhammadiyah Metro, 2025)
Mandai is a fermented food traditionally made from the skin of cempedak fruit. Mandai is one of the typical foods originating from East Kalimantan and South Kalimantan which is usually used as a side dish. However, in the process of processing mandai, food handlers are still in direct contact with the body. This study aims to determine microbial contamination in processed mandai food and to recognize good food safety standards. The research method used was laboratory experimental with MPN, ALT, and Salmonella bacteria tests. The data obtained were analyzed descriptively and compared with SNI 01.2600.1992 and BPOM number 13 of 2019 regarding the limit of microbial contamination in processed food. The results showed that the five samples of mandai from 2-day-old cempedak skin sold in Samarinda city did not meet the requirements, namely the number of coliforms 1100 to >2400 and positive for E.coli and Enterobacter sp. Based on the ALT test, the five samples of 2-day-old mandai did not meet the requirements, which ranged from 1.2 × 108 to 5.3 × 108. All five mandai samples were negative for Salmonella sp.